Design and Compressive Strength Analysis of a Bio-Inspired Cell-Based Lattice - Asistent Prof. Elena Angeleska PhD., Asistent Prof. Blagoja Nestorovski MSc., Ass. Prof. Nikola Avramov PhD., Ass. Prof. Jelena Djokikj PhD. (My University, 2024)
The synergy between state-of-the-art additive manufacturing (AM) technologies and lattice structures offers numerous remarkable advantages which inspire engineers and designers to develop novel high-tech products and systems. By replacing traditional manufacturing methods with AM and conventional materials with architected cellular materials (lattices) an optimization of the mechanical characteristics can be achieved, such as: reduced weight, high strength, good force distribution, high energy absorption, etc. Since lattices are composed of unit cells that repeat regularly to form a periodic geometry, their structure is very controllable. The customization of the unit cell type, size, orientation, arrangement, and other features, directly affects the mechanical properties and the characteristics of the designed lattice product. Therefore, it has been a trend and challenge to experiment by varying the unit cell geometry to examine the change in performance of the lattice structures. In this research, a unique, bio-inspired unit cell was designed and evaluated with a goal to generate a lattice structure with improved compression characteristics. Inspiration was drawn from the seahorse skeleton, which similarly to the lattice geometry, is composed of repeated prism-like segments connected in a manner that allows incredible durability under impact. The new cell design was arranged to form a uniform lattice structure based on a geometric wireframe method. The evaluation procedure was done using an experimental test performed according to the ISO 604:2002(E) standard. The experiment was carried out on 2 types of lattice samples for comparison purposes. The novel lattice showed improved behavior under compression forces.
Keywords: Lattice Structures, Bio-inspired Lattice, Seahorse Skeleton, Lattice Compression, Compression Strength Analysis.